Fatal Neonatal DOLK-CDG as a Rare Form of Syndromic Ichthyosis - Komlosi, Katalin; Claris, Olivier; Collardeau-Frachon, Sophie; Kopp, Julia; Hausser, Ingrid; Mazereeuw-Hautier, Juliette; Jonca, Nathalie; Zimmer, Andreas D.; Sanlaville, Damien; Fischer, Judith (Frontiers in Genetics, 2021)
Neonatal collodion baby or ichthyosis can pose a diagnostic challenge and in many cases only additional organ involvement or the course of the disease will help differentiate between non-syndromic and syndromic forms. Skin abnormalities are described in about 20% of the congenital disorders of glycosylation (CDG). Among those, some rare CDG forms constitute a special group among the syndromic ichthyoses and can initially misdirect the diagnosis towards non-syndromic genodermatosis. DOLK-CDG is such a rare subtype, resulting from a defect in dolichol kinase, in which the congenital skin phenotype (often ichthyosis) is later associated with variable extracutaneous features such as dilatative cardiomyopathy, epilepsy, microcephaly, visual impairment and hypoglycemia and may lead to a fatal course. We report two neonatal cases of lethal ichthyosis from the same family, with distal digital constrictions and a progressive course leading to multi-organ failure and death. Postmortem trio whole-exome sequencing revealed the compound heterozygous variants NM_014908.3: c.1342G>C, p.(Gly448Arg) and NM_014908.3: c.1558A>G, p.(Thr520Ala) in the DOLK gene in the first affected child, which were confirmed in the affected sibling. Reduced staining with anti-α-Dystroglycan antibody was observed in frozen heart tissue of the second child as an expression of reduced O-mannosylation due to the dolichol kinase deficiency. In addition to the detailed dermatopathological changes, both cases presented hepatic and extrahepatic hemosiderosis on histological examination. Our patients represent an early and fatal form of DOLK-CDG with a striking presentation at birth resembling severe collodion baby. Both cases emphasize the phenotypic variability of glycosylation disorders and the importance to broaden the differential diagnosis of ichthyosis and to actively search for organ involvement in neonates with ichthyosis.